Exploring differences among serial, portfolio, and novice entrepreneurs: A study of demographic and psychological factors in micro and small enterprises - Ropęga, Jarosław; Lipińska-Grobelny, Agnieszka (PLOS ONE, 2025)
The aim of this study was to empirically validate selected demographic and psychological factors from Shane’s model in the context of serial and portfolio entrepreneurship. The analysis involved 326 entrepreneurs, including 110 serial entrepreneurs, 105 portfolio entrepreneurs, and 111 novice entrepreneurs (control group). The study employed a survey questionnaire combined with five validated psychological instruments, administered in a manner that enabled control for common method bias. The analysis revealed that two demographic factors—education and having entrepreneurial parents—were statistically significant for distinguishing serial and portfolio entrepreneurs. In terms of personality traits, differences were observed in the levels of psychological capital, suchas: hopefulness, resilience, and also risk-taking propensity, conformity-nonconformity behaviour, with the portfolio entrepreneurs scoring the highest in these areas. This study successfully validates Shane’s model in relation to micro and small-scale entrepreneurship, contributing to a deeper understanding of entrepreneurial behaviour.